Efektivitas Metode Demonstrasi dalam Meningkatkan Pemahaman Konsep Bangun Datar Siswa Kelas III SDN Tanjung Barat - Okta Rosfiani; Wa Ode Adelia Citra Viallo; Dhea Safitri; Ayatullah Said Abdullah (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2025)
According to preliminary findings, class III mathematics instruction at SDN Tanjung Barat 09 that uses lecture and Q&A formats is less successful in producing the best learning results when it comes to flat geometry content. Just 42.3% of pupils have finished studying this content. By using the demonstration technique, this study seeks to address this issue and enhance student learning outcomes. Two cycles of Classroom Action Research (CAR) were conducted. To boost students' active engagement in learning, the demonstration technique was used in conjunction with instructional aids and learning materials like movies in each cycle. and it achieved a really satisfactory 92.31% in the second cycle. This improvement in learning outcomes demonstrates how well the demonstrative method works for teaching flat geometry content. This is because kids may learn visually and kinesthetically through the presentation approach, which makes the concept more tangible and simpler to recall. Additionally, using a variety of instructional resources and learning materials can boost students' willingness to learn.